Preparation method of modified mica insulating material and production process of temperature-resistant mica tape

By adding specific coupling agents and resins to the mica material and performing ball milling treatment, the problem of mica products being easy to decompose and age at high temperatures is solved, and its insulation performance and stability are significantly improved.

CN119763951AActive Publication Date: 2025-04-04SHANGHAI TONGLI ELECTRICAL MATERIALS CO LTD

Patent Information

Application Number
CN202510013297.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-04
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

Mica products are prone to decomposition and aging at high temperatures, resulting in degradation of insulation performance and may even lead to breakdown failures.

Method used

Modified mica insulating material was prepared by adding titanate coupling agent and silane coupling agent to the mica material, and modifying it with bisphenol A epoxy resin, and combining ball milling treatment of aluminum nitride and alumina. This method improves its stability and insulation properties at high temperatures by improving the mechanical and electrical properties of mica materials.

Benefits of technology

It significantly improves the breakdown field strength and resistivity of mica materials at high temperatures, extends the service life of insulating materials, enhances its safety performance, and improves the stability of thermal conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119763951A_ABST
    Figure CN119763951A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of insulating materials, and relates to a preparation method of a modified mica insulating material and a temperature-resistant mica tape production process. -NH2 on the surface of the silane modified mica material is connected with interface amino groups between cyclic carbonate to obtain a hydroxyl polyurethane hybridized mica material, and the hydroxyl polyurethane hybridized mica material is prepared into the calcined mica paper. And starting from the polyester film, respectively obtaining a non-self-adhesive mica tape product and a self-adhesive mica tape product through two different preparation processes. The method comprises the following steps: 1, coating a polyester film with an adhesive, compounding the polyester film with modified calcined mica paper, drying, rolling and slitting to obtain a non-self-adhesive mica tape product; and 2, carrying out corona treatment on the back surface of the polyester film, coating a self-adhesive glue, drying, coating an adhesive, compounding with the modified calcined mica paper, drying, rolling and slitting to obtain the self-adhesive mica tape product. The modified mica tape has excellent insulating property in a high-temperature environment, and aging and decomposition phenomena of the mica layer can be effectively inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of insulating materials, and mainly relates to the preparation of a mica insulating material, and in particular to a preparation method of a modified mica insulating material and a production process of a heat-resistant mica tape. Background Art

[0002] The voltage level of large-scale high-voltage generators can reach up to 27 kV, and the main insulation thickness can reach up to 6~7 mm. The overall size of the motor is huge, and the safe operation life is required to be as long as several decades. However, in the long-term operation of the motor, the main insulation of the motor will continue to be affected by the synergistic effect of multiple stresses, the most important of which is the combined effect of thermal, electrical, environmental and mechanical stresses, which causes the main insulation performance of the motor to slowly age, eventually leading to a complete loss of insulation performance, and even possible breakdown. According to research, about 40% of failures in motors or generators are caused by aging of the main insulation. Therefore, the operating reliability and service life of high-voltage motors depend to a large extent on the main insulation condition of the stator winding. The main insulation material of high-voltage motors is mica tape, which is mainly composed of powdered mica paper, reinforcing materials and adhesives. In order to meet the requirements of high voltage levels and large capacities of high-voltage motors, mica tape is also moving towards The thermal conductivity is getting higher and the thickness is getting thinner.

[0003] Mica tape is a composite insulating material, mainly composed of three materials: dielectric material, reinforcing material, and adhesive. The dielectric material is mainly mica. Mica has high dielectric strength, low loss, high heat resistance, and excellent corona resistance. So far, no insulating material that can replace mica has been found in motor insulation. Mica paper has good electrical insulation, low dielectric loss, and good corona resistance, but its strength is very low. In addition, mica products are prone to decomposition and aging at high temperatures, so further improvements are needed to overcome these problems. Summary of the invention

[0004] In order to solve the problem that mica products are prone to decomposition and aging at high temperatures in the related art, the present invention provides a method for preparing a modified mica insulating material and a production process for a heat-resistant mica tape. The specific operation steps are as follows: S1. Take 30-50 g of calcined muscovite with a particle size of 200-800 mesh and 1-1.5 L of deionized water, stir at a rate of 60-120 rpm for 2-4 h, mix evenly to obtain a calcined muscovite slurry, then heat to 60-110 ° C, add 0.5-1 g of titanate coupling agent JN114, continue stirring for 1-3 h, and after activation, put it into an electric thermostatic blower, set the temperature to 60-110 ° C, and dry it for 6-12 h to obtain activated calcined mica; this step can effectively enhance the activation index of mica, promote the dispersion effect of mica, and promote further effective modification of mica materials by modifying the surface of mica with titanate coupling agent JN114; S2, take 20-30 g of the activated calcined mica in step S1 and 100-200 ml of ethanol-water solution (volume ratio of 1:1), stir continuously at room temperature for 1-3 h, after mixing evenly, use 1.5 mol / L acetic acid solution to adjust the pH of the reaction solution to 3-4, then add 10 g of silane coupling agent KH550, stir continuously for 12-24 h, raise the reaction temperature to 60-80 ° C and continue stirring for 3-5 h, after the reaction is complete, cool the product to room temperature and filter, wash the filter cake with ethanol-water solution 3-5 times, and dry at 60 ° C for 12-24 h to obtain a silane-modified calcined mica material; in this step, the mechanical and electrical properties of the mica material are effectively improved by means of the higher crosslinking density in the organic silicate network in the coupling agent; S3, take 20-30 g of bisphenol A epoxy resin and dissolve it in a mixed solution of 15-30 ml of 2-ethoxyethanol and 5-10 ml of methyl vinyl pyrrolidone, add 0.2-0.5 g of tetraethylammonium bromide and 0.05-0.1 g of anhydrous ZnCl while stirring. 2 After the added substance is completely dissolved, it is transferred to a high-pressure reactor, and then carbon dioxide is introduced for purging 2-3 times. After the gas in the reactor is purged, it is pressurized to 0.4-0.6 MPa with carbon dioxide, and the reaction temperature is set to 100-130 ° C. The reaction is stirred for 12-24 h. After the reaction is completed, the mixed solution is extracted 3-5 times with water-ethyl acetate (volume ratio of 1:3). The final yellow solution obtained is bisphenol A cyclocarbonate; S4, take the bisphenol A cyclic carbonate obtained in step S3 and mix it with 5-10 ml of acetone, stir it at 30-40 ° C for 30-60 min, after it is completely dissolved, add 2-3 ml of isophorone diamine and 0.5-2 ml of 1,8-diazabicyclo [5.4.0] undec-7-ene, reflux and mix at 60-80 ° C for 1-3 h, then add 10-15 g of the silane-modified calcined mica material obtained in step S2, continue to stir for 1-2 h, after the reaction is complete, dry it at 110 ° C for 12 h, and then dry it at 60 ° C for 12 h, then mix the dried material with aluminum nitride and aluminum oxide in a mass ratio of 1:0.1-0.3:0.1-0.3 and ball mill it for 1-2 h, collect the material after ball milling, and obtain a hydroxyl polyurethane hybrid calcined mica material, that is, a modified mica insulating material; in this step, CO 2 As raw materials, a hydroxy polyurethane hybrid mica material is prepared by a non-toxic route, and the synergistic effect of the hydroxy polyurethane and the silane modification in step S3 is fully stimulated, and the -NH 2 The interfacial amino connection between the cyclocarbonate and the cyclocarbonate effectively improves the insulation performance and toughness of the material while maintaining charge dissipation; S5, preparation of modified calcined muscovite paper: pulping: the modified mica insulating material obtained in step S4 is put into a pulping machine, crushed and pulped with high-pressure water at a pressure of 6MPa, and the prepared modified mica pulp is graded and dehydrated with three dewatering screens of 14 mesh, 80 mesh and 200 mesh, and the obtained 14-80 mesh coarse pulp and 80-200 mesh fine pulp enter the pulp storage tank and are stored separately for standby; papermaking: regulating the sizing order of the modified mica coarse pulp and the modified mica fine pulp, sequentially performing the first sizing of the modified mica fine pulp, the sizing of the modified mica coarse pulp, and then the second sizing of the mica fine pulp, and finally performing round-net papermaking, drying the prepared modified mica paper, and drying to a moisture content of 0.2%-0.5% to obtain modified calcined muscovite paper, wherein the sizing amount of the modified mica fine pulp is the same for the two times, and the mass ratio of the mica coarse pulp to the mica fine pulp during sizing is controlled to be 1-2:1; S6. Preparation of non-self-adhesive mica tape: a polyester film (purchased from Henan Dongjue Electric Co., Ltd.) is coated with an adhesive (purchased from Shandong Guohua Chemical Co., Ltd.) and then laminated with modified calcined mica paper under heating and pressure at 100-150°C, and then dried, rolled and slit to obtain a non-self-adhesive mica tape product; S7. Preparation of self-adhesive mica tape: corona-treat the back of the polyester film, apply self-adhesive glue and then dry, apply adhesive and heat and pressurize the modified calcined mica paper at 100-150°C to compound, and then dry, roll and slit to obtain a self-adhesive mica tape product.

[0005] Preferably: the muscovite particles in step S1 have a size of 400 mesh.

[0006] Preferably, the amount of titanate coupling agent JN114 added in step S1 is 0.7 g.

[0007] Preferably, the amount of activated mica added in step S2 is 20 g.

[0008] Preferably, the carbon dioxide pressure in step S3 is 0.6 MPa.

[0009] Preferably, the amount of isophoronediamine added in step S4 is 2.8 ml.

[0010] Preferably, in step S5, the mold is first heated to 80-110°C, the pressure is 0.6 MPa and the duration is 45s, secondly heated to 120-150°C, the pressure is 0.8 MPa and the duration is 140s, and thirdly cooled to room temperature at a cooling rate of 10°C / min.

[0011] Preferably, in step S6, the polyester film is coated with an adhesive and then laminated with the modified calcined mica paper under heating and pressure at 100-150°C.

[0012] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention has excellent breakdown field strength and resistivity at high temperature.

[0013] 2. The present invention is generally applicable to conductors and main insulation or supporting insulation materials.

[0014] 3. The mica tape of the present invention has good thermal stability and higher safety performance.

[0015] 4. Through a special sizing sequence, the electrical strength and tensile strength of mica paper are enhanced. The fine scales on the surface cover the unevenness of the coarse scales, further enhancing the electrical strength of mica paper and making the surface smoother and smoother. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0017] Figure 1 The present invention is a process flow chart for preparing mica tape products.

[0018] Figure 2This is a graph showing the tensile strength of the modified calcined mica paper prepared in the present invention.

[0019] Figure 3 This is a diagram showing the tear strength of the modified calcined mica paper prepared in the present invention.

[0020] Figure 4 Thermal conductivity diagram of the self-adhesive mica tapes prepared in Examples 1, 2 and 4 and Comparative Examples 2, 3, 6 and 7 after aging.

[0021] Figure 5 The breakdown field strength diagram of the self-adhesive mica tapes prepared in Examples 1, 2 and 4 and Comparative Examples 2, 3, 6 and 7 of the present invention after aging. DETAILED DESCRIPTION

[0022] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the content of the present invention and are not used to limit the present invention.

[0023] The embodiment can obtain two products, one: non-self-adhesive mica tape product; the other: self-adhesive mica tape product; the product preparation flow chart is shown in Figure 1 shown.

[0024] Example 1

[0025] S1. Take 30 g of calcined muscovite with a particle size of 200 mesh and 1 L of deionized water and stir at a rate of 60 rpm for 2 h to obtain a calcined muscovite slurry. Then heat it to 60°C, add 0.5 g of titanate coupling agent JN114, continue stirring for 1 h, and after activation, put it into an electric thermostatic blower, set the temperature to 60°C, and dry it for 6 h to obtain activated calcined mica. S2, take 20 g of the activated calcined mica in step S1 and mix it with 100 ml of ethanol-water solution (volume ratio is 1:1), stir it continuously at room temperature for 1 hour, after it is evenly mixed, use 1.5 mol / L acetic acid solution to adjust the pH of the reaction solution to 3, then add 10 g of silane coupling agent KH550, stir it continuously for 12 hours, raise the reaction temperature to 60 ° C and continue stirring for 3 hours, after the reaction is complete, cool the product to room temperature and filter it, wash the filter cake with ethanol-water solution 3 times, and dry it at 60 ° C for 12 hours to obtain silane-modified calcined mica material; S3, take 20 g of bisphenol A epoxy resin and dissolve it in a mixed solution of 15 ml of 2-ethoxyethanol and 5 ml of methyl vinyl pyrrolidone, add 0.2 g of tetraethylammonium bromide and 0.05 g of anhydrous ZnCl while stirring. 2 After the added substance is completely dissolved, it is transferred to a high-pressure reactor, and then carbon dioxide is introduced for purging twice. After the gas in the reactor is purged clean, it is pressurized to 0.4MPa with carbon dioxide, and the reaction temperature is set to 100°C. The reaction is stirred for 12 hours. After the reaction is completed, the mixed solution is extracted three times with water-ethyl acetate (volume ratio of 1:3). The final yellow solution obtained is bisphenol A cyclocarbonate; S4, take the bisphenol A cyclic carbonate obtained in step S3 and mix it with 5 ml of acetone, stir it at 30°C for 30 minutes, and after it is completely dissolved, add 2 ml of isophorone diamine and 0.5 ml of 1,8-diazabicyclo[5.4.0]undec-7-ene, reflux and mix at 60°C for 1 hour, then add 10 g of the silane-modified calcined mica material obtained in step S2, continue to stir for 1 hour, after the reaction is complete, dry it at 110°C for 12 hours and at 60°C for 12 hours, then mix the dried material with aluminum nitride and aluminum oxide in a mass ratio of 1:0.2:0.1 and ball mill it for 1.5 hours, collect the material after ball milling, and obtain the hydroxyl polyurethane hybrid calcined mica material; S5, preparation of modified calcined muscovite paper: pulping: the modified mica insulating material obtained in step S4 is put into a pulping machine, crushed and pulped with high-pressure water at a pressure of 6MPa, and the prepared modified mica pulp is graded and dehydrated with three dewatering screens of 14 mesh, 80 mesh, and 200 mesh, so that 14-80 mesh coarse pulp and 80-200 mesh fine pulp can be obtained and enter the pulp storage tank for storage and standby; papermaking: regulating the sizing order of the modified mica coarse pulp and the modified mica fine pulp, sequentially performing the first sizing of the modified mica fine pulp, the sizing of the modified mica coarse pulp, and then the second sizing of the mica fine pulp, and finally performing round-net papermaking, drying the prepared modified mica paper, and drying to a moisture content of 0.2% to obtain modified calcined muscovite paper, wherein the sizing amount of the modified mica fine pulp is the same for the two times, and the mass ratio of the mica coarse pulp to the mica fine pulp during sizing is controlled to be 1.5:1; S6, preparation of non-self-adhesive mica tape: coating a polyester film with an adhesive and then heating and pressurizing the modified calcined mica paper obtained in step S5 at 100° C., and then drying, winding and slitting to obtain a non-self-adhesive mica tape product; S7. Preparation of self-adhesive mica tape: corona-treating the back of the polyester film, coating it with self-adhesive and drying it, coating it with adhesive after drying, heating and pressurizing it with the modified calcined mica paper obtained in step S5 at 100° C., and then drying, winding and slitting to obtain a self-adhesive mica tape product.

[0026] Comparative Example 1: Except that titanate coupling agent JN114 is not used for activation in step S1, the rest is the same as Example 1.

[0027] Comparative Example 2: Except that silane coupling agent KH550 is not added in step S2, the rest is the same as Example 1.

[0028] Example 2

[0029] S1. Take 50 g of calcined muscovite with a particle size of 800 mesh and stir it with 1.5 L of deionized water at a rate of 120 rpm for 4 h to obtain a calcined muscovite slurry. Then heat it to 110 °C, add 1 g of titanate coupling agent JN114, and continue stirring for 3 h. After activation, put it into an electric thermostatic blower, set the temperature to 110 °C, and dry it for 12 h to obtain activated calcined mica. S2, take 30 g of the activated calcined mica in step S1 and mix it with 200 ml of ethanol-water solution (volume ratio is 1:1), stir it continuously at room temperature for 3 h, after it is evenly mixed, use 1.5 mol / L acetic acid solution to adjust the pH of the reaction solution to 4, then add 10 g of silane coupling agent KH550, stir it continuously for 24 h, raise the reaction temperature to 80 ° C and continue stirring for 5 h, after the reaction is complete, cool the product to room temperature and filter it, wash the filter cake with ethanol-water solution 5 times, and dry it at 60 ° C for 24 h to obtain silane-modified calcined mica material; S3, take 24 g of bisphenol A epoxy resin and dissolve it in a mixed solution of 30 ml of 2-ethoxyethanol and 10 ml of methyl vinyl pyrrolidone, add 0.5 g of tetraethylammonium bromide and 0.1 g of anhydrous ZnCl while stirring. 2 After the added substance is completely dissolved, it is transferred to a high-pressure reactor, and then carbon dioxide is introduced for purging 3 times. After the gas in the reactor is purged, it is pressurized to 0.6 MPa with carbon dioxide, and the reaction temperature is set to 130 °C. The reaction is stirred for 24 h. After the reaction is completed, the mixed solution is extracted 5 times with water-ethyl acetate (volume ratio of 1:3). The final yellow solution obtained is bisphenol A cyclocarbonate; S4, taking the bisphenol A cyclocarbonate obtained in step S3 and mixing it with 7 ml of acetone, stirring at 40°C for 60 min, after it is completely dissolved, adding 3 ml of isophorone diamine and 2 ml of 1,8-diazabicyclo[5.4.0]undec-7-ene, reflux mixing at 80°C for 3 h, then adding 15 g of the silane-modified calcined mica material obtained in step S2, continuing to stir for 2 h, after the reaction is complete, drying it at 110°C for 12 h and at 60°C for 12 h, then mixing the dried material with aluminum nitride and aluminum oxide in a mass ratio of 1:0.1:0.2 and ball milling for 2 h, collecting the material after ball milling, and obtaining a hydroxyl polyurethane hybrid calcined mica material; S5, preparation of modified calcined muscovite paper: pulping: the modified mica insulating material obtained in step S4 is put into a pulping machine, crushed and pulped with high-pressure water at a pressure of 6MPa, and the prepared modified mica pulp is graded and dehydrated with three dewatering screens of 14 mesh, 80 mesh, and 200 mesh, so that 14-80 mesh coarse pulp and 80-200 mesh fine pulp can be obtained and enter the pulp storage tank for storage and standby; papermaking: the sizing order of the modified mica coarse pulp and the modified mica fine pulp is adjusted, and the first sizing of the modified mica fine pulp, the sizing of the modified mica coarse pulp, and the second sizing of the mica fine pulp are carried out in sequence, and finally the rotary screen papermaking is carried out, and the prepared modified mica paper is dried to a moisture content of 0.5% to obtain the modified calcined muscovite paper, wherein the sizing amount of the modified mica fine pulp is the same for the two times, and the mass ratio of the mica coarse pulp to the mica fine pulp during sizing is controlled to be 2:1; S6, preparation of non-self-adhesive mica tape: coating a polyester film with an adhesive, heating and pressurizing the composite with the modified calcined mica paper obtained in step S5 at 150° C., and then drying, winding and slitting to obtain a non-self-adhesive mica tape product; S7. Preparation of self-adhesive mica tape: corona-treating the back of the polyester film, coating it with self-adhesive and drying it, coating it with adhesive after drying, heating and pressurizing it with the modified calcined mica paper obtained in step S5 at 150°C, and then drying, winding and slitting to obtain a self-adhesive mica tape product.

[0030] Comparative Example 3: Except that bisphenol A cyclocarbonate is not used to modify the calcined muscovite in step S4, the rest is the same as Example 2.

[0031] Example 3

[0032] S1. Take 40 g of calcined muscovite with a particle size of 500 mesh and stir it with 1.25 L of deionized water at a rate of 100 rpm for 3 h to obtain a calcined muscovite slurry. Then heat it to 120 °C, add 0.5-1 g of titanate coupling agent JN114, continue stirring for 2 h, and after activation, put it into an electric thermostatic blower, set the temperature to 100 °C, and dry it for 10 h to obtain activated calcined mica. S2, take 25 g of the activated calcined mica in step S1 and mix it with 150 ml of ethanol-water solution (volume ratio is 1:1), stir it continuously at room temperature for 2 h, after it is evenly mixed, use 1.5 mol / L acetic acid solution to adjust the pH of the reaction solution to 3.5, then add 10 g of silane coupling agent KH550, stir it continuously for 18 h, raise the reaction temperature to 70°C and continue stirring for 4 h, after the reaction is complete, cool the product to room temperature and filter it, wash the filter cake with ethanol-water solution 4 times, and dry it at 60°C for 18 h to obtain silane-modified calcined mica material; S3, take 25 g of bisphenol A epoxy resin and dissolve it in a mixed solution of 20 ml of 2-ethoxyethanol and 7 ml of methyl vinyl pyrrolidone, add 0.3 g of tetraethylammonium bromide and 0.06 g of anhydrous ZnCl while stirring. 2 After the added substance is completely dissolved, it is transferred to a high-pressure reactor, and then carbon dioxide is introduced for purging twice. After the gas in the reactor is purged, it is pressurized to 0.5 MPa with carbon dioxide, and the reaction temperature is set to 120 °C. The reaction is stirred for 18 h. After the reaction is completed, the mixed solution is extracted 4 times with water-ethyl acetate (volume ratio of 1:3). The final yellow solution obtained is bisphenol A cyclocarbonate; S4, taking the bisphenol A cyclic carbonate obtained in step S3 and mixing it with 7 ml of acetone, stirring at 35°C for 35 minutes, after complete dissolution, adding 2 ml of isophorone diamine and 0.8 ml of 1,8-diazabicyclo[5.4.0]undec-7-ene, reflux mixing at 70°C for 2 hours, then adding 14 g of the silane-modified calcined mica material obtained in step S2, continuing to stir for 1 hour, after the reaction is complete, drying it at 110°C for 12 hours and at 60°C for 12 hours, then mixing the dried material with aluminum nitride and aluminum oxide in a mass ratio of 1:0.2:0.3 and ball milling for 1 hour, collecting the material after ball milling, and obtaining a hydroxyl polyurethane hybrid calcined mica material; S5, preparation of modified calcined muscovite paper: pulping: the modified mica insulating material obtained in step S4 is put into a pulping machine, crushed and pulped with high-pressure water at a pressure of 6MPa, and the prepared modified mica pulp is graded and dehydrated with three dewatering screens of 14 mesh, 80 mesh, and 200 mesh, so that 14-80 mesh coarse pulp and 80-200 mesh fine pulp can be obtained and enter the pulp storage tank for storage and standby; papermaking: regulating the sizing order of the modified mica coarse pulp and the modified mica fine pulp, sequentially performing the first sizing of the modified mica fine pulp, the sizing of the modified mica coarse pulp, and then the second sizing of the mica fine pulp, and finally performing round-net papermaking, drying the prepared modified mica paper, and drying to a moisture content of 0.3% to obtain modified calcined muscovite paper, wherein the sizing amount of the modified mica fine pulp is the same for the two times, and the mass ratio of the mica coarse pulp to the mica fine pulp during sizing is controlled to be 1.7:1; S6. Preparation of non-self-adhesive mica tape: coating a polyester film with an adhesive and then laminating it with a modified calcined mica paper under heating and pressure at 120° C., and then drying, winding and slitting to obtain a non-self-adhesive mica tape product; S7. Preparation of self-adhesive mica tape: corona-treat the back of the polyester film, apply self-adhesive glue and then dry it, apply adhesive and heat and pressurize the modified calcined mica paper at 120°C to compound it, and then dry, roll and slit it to obtain a self-adhesive mica tape product.

[0033] Comparative Example 4: Except that coarse pulp is used for sizing in step S5, the rest is the same as Example 3.

[0034] Comparative Example 5: Except that fine pulp is used for sizing in step S5, the rest is the same as Example 3.

[0035] Example 4

[0036] S1. Take 33 g of calcined muscovite with a particle size of 230 mesh and 1.3 L of deionized water and stir at a rate of 110 rpm for 2.5 h to obtain a calcined muscovite slurry. Then heat it to 90 °C, add 0.9 g of titanate coupling agent JN114, continue stirring for 1.5 h, and after activation, put it into an electric thermostatic blower, set the temperature to 90 °C, and dry it for 9 h to obtain activated calcined mica. S2, take 23 g of the activated calcined mica in step S1 and mix it with 130 ml of ethanol-water solution (volume ratio is 1:1), stir it continuously at room temperature for 3 h, after it is evenly mixed, use 1.5 mol / L acetic acid solution to adjust the pH of the reaction solution to 3.5, then add 10 g of silane coupling agent KH550, stir it continuously for 16 h, raise the reaction temperature to 65 ° C and continue stirring for 3.5 h, after the reaction is complete, cool the product to room temperature and filter it, wash the filter cake with ethanol-water solution 3.5 times, and dry it at 60 ° C for 16 h to obtain silane-modified calcined mica material; S3, take 23g of bisphenol A epoxy resin and dissolve it in a mixed solution of 25ml of 2-ethoxyethanol and 9ml of methyl vinyl pyrrolidone, add 0.37g of tetraethylammonium bromide and 0.08g of anhydrous ZnCl while stirring. 2 After the added substance is completely dissolved, it is transferred to a high-pressure reactor, and then carbon dioxide is introduced for purging twice. After the gas in the reactor is purged, it is pressurized to 0.45 MPa with carbon dioxide, and the reaction temperature is set to 110 °C. The reaction is stirred for 16 hours. After the reaction is completed, the mixed solution is extracted 4 times with water-ethyl acetate (volume ratio of 1:3). The final yellow solution obtained is bisphenol A cyclocarbonate; S4, taking the bisphenol A cyclic carbonate obtained in step S3 and mixing it with 7 ml of acetone, stirring at 37°C for 55 min, after complete dissolution, adding 2 ml of isophorone diamine and 1.6 ml of 1,8-diazabicyclo[5.4.0]undec-7-ene, reflux mixing at 65°C for 2 h, then adding 13 g of the silane-modified calcined mica material obtained in step S2, continuing to stir for 1 h, after the reaction is complete, drying it at 110°C for 12 h and at 60°C for 12 h, then mixing the dried material with aluminum nitride and aluminum oxide in a mass ratio of 1:0.1:0.3 and ball milling for 1 h, collecting the material after ball milling, and obtaining a hydroxyl polyurethane hybrid calcined mica material; S5, preparation of modified calcined muscovite paper: pulping: the modified mica insulating material obtained in step S4 is put into a pulping machine, crushed and pulped with high-pressure water at a pressure of 6MPa, and the prepared modified mica pulp is graded and dehydrated with three dewatering screens of 14 mesh, 80 mesh, and 200 mesh, so that 14-80 mesh coarse pulp and 80-200 mesh fine pulp can be obtained and enter the pulp storage tank for storage and standby; papermaking: regulating the sizing order of the modified mica coarse pulp and the modified mica fine pulp, sequentially performing the first sizing of the modified mica fine pulp, the sizing of the modified mica coarse pulp, and then the second sizing of the mica fine pulp, and finally performing round-net papermaking, drying the prepared modified mica paper, and drying to a moisture content of 0.4% to obtain modified calcined muscovite paper, wherein the sizing amount of the modified mica fine pulp is the same for the two times, and the mass ratio of the mica coarse pulp to the mica fine pulp during sizing is controlled to be 1.8:1; S6. Preparation of non-self-adhesive mica tape: coating a polyester film with an adhesive and then laminating the film with a modified calcined mica paper under heating and pressure at 150° C., followed by drying, winding and slitting to obtain a non-self-adhesive mica tape product; S7. Preparation of self-adhesive mica tape: corona-treat the back of the polyester film, apply self-adhesive glue and then dry it, apply adhesive and heat and pressurize the modified calcined mica paper at 150°C after drying, and then dry, roll up and slit to obtain a self-adhesive mica tape product.

[0037] Comparative Example 6: Except that aluminum nitride is not added in step S4, the rest is the same as Example 4.

[0038] Comparative Example 7: Except that alumina is not added in step S4, the rest is the same as Example 4.

[0039] Test method: The mechanical properties of the modified calcined mica paper obtained in Examples 1-4, Comparative Example 1, Comparative Example 4, and Comparative Example 5 were tested. The method is as follows: Tensile strength test: Tensile strength test usually refers to stretching a material until it breaks to measure the maximum stress it can withstand, thereby evaluating the mechanical properties of the material. First, cut or form a sample of a specific size according to the test standard, usually in the shape of a strip or dog bone. Mount the sample on a universal material testing machine, making sure that the clamps fix both ends of the sample, and then start stretching the sample until it breaks, recording the stress (force divided by the original cross-sectional area) and strain (elongation divided by the original length) of the sample. The maximum stress that a material can withstand during stretching is usually measured in Pascals (Pa) or Megapascals (MPa). The calculation formula is as follows: Tensile strength ( σ )=F / A 0 , where F is the maximum force that the sample withstands when it breaks, in N; A 0 is the original cross-sectional area of ​​the sample (square centimeters, cm²).

[0040] Tear strength test: Cut the material into samples of specific size, usually rectangular or circular, fix one side of the sample in the upper fixture of the tear tester, leave a part of the other side of the sample for tearing, apply a gradually increasing force at the free end of the sample, this force is perpendicular to the edge of the sample to simulate the tearing process, continue to increase the load until the sample tears, record the maximum load during the tearing process, record the maximum load during the tearing process and the size of the sample; tear strength = F max / L, where Fmax is the maximum load recorded when the sample is torn, in N; L is the length of the torn portion of the sample, in cm. The test results are shown in Table 1.

[0041] The thermal conductivity, volume resistivity and breakdown field strength of the non-self-adhesive mica tape products and the self-adhesive mica tape products obtained in Examples 1-4 and Comparative Examples 1-7 were tested as follows: Thermal conductivity measurement: Thermal conductivity is an important property of mica tape. Improving its thermal conductivity is closely related to improving the motor level and reducing the temperature rise of the motor winding. The thermal conductivity test instrument used in this experiment is the LFA447 Nanoflash laser flash thermal conductivity meter produced by NetzschGeratebau GmbH in Germany, which tests the longitudinal thermal conductivity of mica tape.

[0042] The thermal conductivity is given by the formula: l =a ´ C p ´ r , where: α is the thermal diffusion coefficient, C p is the specific heat capacity, and ρ is the density of the film sample.

[0043] Volume resistivity measurement: Volume resistivity refers to the ratio of the DC voltage applied to the two surfaces of the insulating material per unit volume to the steady-state current passing through the insulating material, expressed as ρ v =R v · A / h Indicates that ρ v Refers to volume resistivity, the unit is Ω·cm; R v Refers to volume resistance, the unit is Ω; A Refers to the effective area of ​​the measuring electrode, in cm 2 , h Refers to the average thickness of the sample, in cm.

[0044] Breakdown field strength measurement: The ZJC-KV instrument manufactured by Beijing AVIC Times Instrument Equipment Co., Ltd. was used to test the breakdown strength. The experiment was carried out in air, and the voltage increase rate at the power frequency was 0.2kV / s. The breakdown voltage obtained in the experiment was in kV, and then divided by the thickness of the paper to obtain the breakdown strength in kV / mm. The breakdown strength was calculated according to the formula E=U / d, where E is the breakdown strength, kV / mm; U is the breakdown voltage, kV; and d is the paper thickness, mm. The test results are shown in Tables 2 and 3.

[0045] Table 1 Properties of modified calcined mica paper

[0046] Table 2 Non-self-adhesive mica tape product properties

[0047] Table 3 Product performance of self-adhesive mica tape

[0048] According to Table 1, Figure 2 and Figure 3 From the performance of the modified calcined mica paper, it can be seen that the titanate coupling agent JN114 can effectively activate the mica surface, so that the silane coupling agent KH550 and bisphenol A cyclic carbonate can be more combined with mica to improve the toughness of the mica paper. At the same time, the method of alternating fine pulp and coarse pulp sizing can obtain mica paper with better tensile strength and tear strength.

[0049] According to the results in Table 2 and Table 3, the thermal conductivity, volume resistivity and breakdown field strength of the non-self-adhesive mica and self-adhesive mica paper obtained in the embodiment are not very different. According to the comparison between the results of Comparative Examples 6 and 7 and the embodiment, it can be seen that after aluminum nitride and aluminum oxide are ball-milled and mixed with the modified calcined mica, the thermal conductivity of the mica tape is significantly improved due to the synergistic effect between aluminum nitride and aluminum oxide, so that the mica tape can dissipate heat in time to prevent aging due to excessive temperature. At the same time, according to the comparison between the results of Comparative Examples 2 and 3 and the embodiment, it can be seen that there is a synergistic effect between the silane coupling agent KH550 and bisphenol A cyclocarbonate, which can effectively improve the insulation performance of the mica tape.

[0050] Accelerated aging simulation test: The self-adhesive mica tape samples prepared in Example 1, Example 2, Example 4, Comparative Example 2, Comparative Example 3, Comparative Example 6 and Comparative Example 7 were respectively irradiated with continuous light from 3×2.0kW xenon lamp tubes at an average radiation intensity of 550W / m 2 ; Temperature is (180±5)℃; Light source-sample distance is 100-300mm; Aging time is 30d, and samples are taken every 10d to test the thermal conductivity, volume resistivity and breakdown field strength of these samples. The test results are as follows Figure 4 ,5 And as shown in Table 4.

[0051] according to Figure 4 , Figure 5 As shown in Table 4, after 30 days of aging test, it can be seen that the sample prepared in Example 3 has excellent anti-aging performance. According to the comparison of the results of Comparative Examples 2 and 3 with the results of Examples 1 and 2, the volume resistivity and breakdown field strength of the products obtained in Examples 1 and 2 do not change much after aging for 30 days due to the synergistic effect between the silane coupling agent KH550 and the bisphenol A cyclic carbonate. In contrast, not only the initial thermal conductivity, volume resistivity and breakdown field strength of Comparative Examples 2 and 3 are significantly reduced, but also the values ​​of volume resistivity and breakdown field strength are also reduced after aging for 30 days. Figure 4 , 5 By comparing the results of Comparative Examples 6 and 7 in Table 4 with the results of Example 4, it can be seen that after 30 days of aging test, the thermal conductivity of Comparative Examples 6 and 7 is significantly reduced, while the thermal conductivity of Example 4 does not change much, indicating that the addition of aluminum nitride and aluminum oxide also has certain synergistic anti-aging properties, which can enable the thermal conductivity of the sample prepared in Example 4 to maintain a high level after 30 days of aging.

[0052] Table 4

[0053] High temperature resistance test: The modified calcined mica paper prepared in Example 4, Comparative Example 6 and Comparative Example 7 was heated to 500°C in a muffle furnace for 50 hours for high temperature resistance test. After the test, the thermal conductivity, volume resistivity and breakdown field strength of the modified calcined mica paper prepared in Example 4, Comparative Example 6 and Comparative Example 7 were tested. The results are shown in Table 5.

[0054] Table 5

[0055] According to Table 5, after the modified calcined mica paper prepared in Example 4 was calcined at 500°C for 60 hours, its thermal conductivity, volume resistivity and breakdown field strength were almost unchanged compared with the original mica paper, while the thermal conductivity, volume resistivity and breakdown field strength of Comparative Examples 6 and 7 were significantly reduced, further proving the synergistic effect between aluminum nitride and aluminum oxide, which can effectively improve the high temperature resistance of mica paper.

[0056] The above-mentioned embodiments only express the specific implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present invention. It should be pointed out that, for those skilled in the art, without departing from the concept of the present invention, any other changes, modifications, substitutions, combinations, simplifications made without departing from the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a modified mica insulating material, characterized in that: The specific synthesis steps are as follows: S1. Take 30-50 g of calcined muscovite with a particle size of 200-800 mesh and stir with 1-1.5 L of deionized water at a rate of 60-120 rpm for 2-4 h to obtain a calcined muscovite slurry. Then heat it to 60-110 ° C, add 0.5-1 g of titanate coupling agent JN114, continue stirring for 1-3 h, and after activation, put it into an electric thermostatic blower, set the temperature to 60-110 ° C, and dry it for 6-12 h to obtain activated calcined mica; S2, take 20-30 g of the activated calcined mica in step S1 and 100-200 ml of ethanol-water solution (volume ratio of 1:1), stir continuously at room temperature for 1-3 h, after mixing evenly, use 1.5 mol / L acetic acid solution to adjust the pH of the reaction solution to 3-4, then add 10 g of silane coupling agent KH550, continue stirring for 12-24 h, raise the reaction temperature to 60-80 ° C and continue stirring for 3-5 h, after the reaction is complete, cool the product to room temperature and filter, wash the filter cake with ethanol-water solution 3-5 times, and dry it at 60 ° C for 12-24 h to obtain silane-modified calcined mica material; S3, take 20-30 g of bisphenol A epoxy resin and dissolve it in a mixed solution of 15-30 ml of 2-ethoxyethanol and 5-10 ml of methyl vinyl pyrrolidone, add 0.2-0.5 g of tetraethylammonium bromide and 0.05-0.1 g of anhydrous ZnCl2 while stirring, after the added substances are completely dissolved, transfer to a high-pressure reactor, then pass carbon dioxide to purge 2-3 times, after the gas in the reactor is purged clean, pressurize it to 0.4-0.6 MPa with carbon dioxide, set the reaction temperature to 100-130°C, stir the reaction for 12-24 h, after the reaction is completed, use water-ethyl acetate (volume ratio of 1:3) to extract the mixed solution 3-5 times, and the final yellow solution obtained is bisphenol A cyclocarbonate; S4. Mix the bisphenol A cyclic carbonate obtained in step S3 with 5-10 ml of acetone, stir at 30-40 °C for 30-60 min, and after complete dissolution, add 2-3 ml of isophorone diamine and 0.5-2 ml of 1,8-diazabicyclo[5.4.0]undec-7-ene, reflux and mix at 60-80 °C for 1-3 h, then add 10-15 g of the silane-modified calcined mica material obtained in step S2, continue stirring for 1-2 h, and after the reaction is complete, dry it at 110 °C for 12 h and at 60 °C for 12 h, then mix the dried material with aluminum nitride and aluminum oxide in a mass ratio of 1:0.1-0.3:0.1-0.3 and ball mill for 1-2 h. After the ball milling is completed, collect the material to obtain a hydroxyl polyurethane hybrid calcined mica material, i.e., a modified mica insulating material.

2. The method for preparing a modified mica insulating material according to claim 1, characterized in that: The particle size of the calcined muscovite in step S1 is 400 mesh.

3. The method for preparing a modified mica insulating material according to claim 2, characterized in that: The amount of titanate coupling agent JN114 added in step S1 is 0.7 g.

4. The method for preparing a modified mica insulating material according to claim 2, characterized in that: The amount of activated mica added in step S2 is 20 g.

5. The method for preparing a modified mica insulating material according to claim 3, characterized in that: The carbon dioxide pressure in step S3 is 0.6 MPa.

6. The method for preparing a modified mica insulating material according to claim 4, characterized in that: The amount of isophoronediamine added in step S4 is 2.8 ml.

7. A heat-resistant mica tape, characterized in that: The modified mica insulating material is prepared by the method for preparing a modified mica insulating material according to any one of claims 1 to 6.

8. A production process for the heat-resistant mica tape according to claim 7, characterized in that: The following steps are involved: S5. Preparation of modified calcined muscovite paper: Pulping: Put the modified mica insulating material prepared by the method for preparing a modified mica insulating material according to any one of claims 1 to 6 into a pulping machine, crush and pulp it with high-pressure water at a pressure of 6 MPa, and grade and dehydrate the prepared modified mica pulp with three dewatering screens of 14 mesh, 80 mesh, and 200 mesh, and the obtained 14-80 mesh coarse pulp and 80-200 mesh fine pulp are put into a pulp storage tank and stored separately for standby use; Papermaking: regulating the sizing order of modified mica coarse pulp and modified mica fine pulp, sequentially performing the first sizing of modified mica fine pulp, the sizing of modified mica coarse pulp, and then the second sizing of mica fine pulp, and finally performing round-net papermaking, drying the prepared modified mica paper, and drying to a moisture content of 0.2%-0.5% to obtain modified calcined muscovite mica paper, wherein the sizing amount of the modified mica fine pulp is the same for the two times, and the mass ratio of the mica coarse pulp to the mica fine pulp during sizing is controlled to be 1-2:1; S6. Preparation of non-self-adhesive mica tape: coating a polyester film with an adhesive and then laminating it with a modified calcined mica paper under heating and pressure at 100-150° C., and then drying, winding and slitting to obtain a non-self-adhesive mica tape product; S7. Preparation of self-adhesive mica tape: corona-treat the back of the polyester film, apply self-adhesive glue and then dry, apply adhesive and heat and pressurize the modified calcined mica paper at 100-150°C to compound, and then dry, roll and slit to obtain a self-adhesive mica tape product.

9. The production process of a heat-resistant mica tape according to claim 8, characterized in that: In step S5, the mold is first heated to 80-110°C, the pressure is 0.6 MPa and the duration is 45 seconds, secondly heated to 120-150°C, the pressure is 0.8 MPa and the duration is 140 seconds, and thirdly cooled to room temperature at a cooling rate of 10°C / min.

10. The production process of a heat-resistant mica tape according to claim 8, characterized in that: In the step S6, the polyester film is coated with an adhesive and then laminated with the modified calcined mica paper under heating and pressure at 120°C.

Citation Information

Patent Citations

  • Inorganic powder mica paper and preparation method and use thereof

    CN103757977A

  • Preparation method of active mica paper and related products thereof

    CN112796151A

  • Corona-resistant mica / aramid fiber mixed paper for new energy automobile and preparation method of corona-resistant mica / aramid fiber mixed paper

    CN115584660A

  • High-heat-resistance mica tape and manufacturing method thereof

    CN116259456A

  • Modified mica powder / resin composite insulating material, preparation process thereof and preparation process of mica coil

    CN118919191A

Cited By

  • High-thermal-conductivity insulating less-glue mica tape and preparation method thereof

    CN120327046A

  • A high thermal conductivity, insulation, and low-resistance mica tape and its preparation method

    CN120327046B